Analisis Strategi Tiga Pilar Gizi Desa Sebagai Usaha Penanggulangan Stunting Desa Jogomulyo Melalui Rangkaian Kegiatan - Dila Resti Kamila; Kartika Wahyu Prasetyaningsih; Niken Dyah Ayuning Tiaz; Resnandy Akmal Pratama; Syifa Hanin Khusnunnisa; Sri Hastuti (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
The Three Pillars of Village Nutrition Program is an initiative carried out in Jogomulyo Village to tackle the problem of stunting through outreach and education. This activity includes outreach about stunting, providing folic acid tablets and additional food to pregnant women, as well as providing blood supplement tablets to young women. The aim of this community service activity is to provide education to pregnant women, young women and the community about the importance of adequate nutrition to prevent stunting. The first method is carried out by providing information about stunting and balanced nutrition to pregnant women and posyandu participants. Evaluate the assessment by means of a pre-test first, followed by material and a post-test. The results of providing the material increased from 84,5 to 93,6. The second method was carried out by distributing blood supplement tablets, folic acid and additional food door to door. This activity was carried out in Kliwonnan Hamlet, Jogomulyo Village, Tempuran District, Magelang Regency. The success of this program shows that nutritional support can help reduce the risk of stunting by increasing awareness of the importance of balanced nutrition.